Does farmer group membership improve technology adoption and household welfare? Evidence from Tanzania - Manda, J.; Mmbando, E.; Feleke, S.; Kotu, B.; Varma, P. (2025)
revious studies have demonstrated that membership in farmer groups (MFGs) promotes the adoption of improved agricultural technologies, increases farm incomes, and alleviates poverty. However, these studies often neglect the variability in treatment effects, concentrating primarily on average treatment effects. They also typically rely on single technological components and unidimensional, income-based outcome variables, failing to capture technology adoption and multidimensional poverty comprehensively. In contrast, this article evaluates the effects of MFGs among farmers indifferent to membership (marginal treatment effects, MTEs), distinguishing group membership effects based on observable and unobservable heterogeneity. It also incorporates integrated technological components and multidimensional poverty measures. Analyzing data from a survey of 579 households in Tanzania reveals that MFGs increase the adoption of integrated soil fertility management (ISFM) practices by 31%, improve dietary diversity by 10%, and reduce multidimensional poverty by 5% among members. These effects vary due to differences in unobserved member characteristics. The results support MFGs as a valuable component of agricultural development strategies to enhance technology adoption, income growth, nutritional diversity, and poverty reduction. Given the heterogeneous effects, policymakers should tailor strategies to engage suitable households. Furthermore, the higher potential impact on non-members suggests targeted outreach efforts to maximize the benefits of MFGs